Endoscopic Evaluation of 2484 Patients with Upper GI Haemorrhage - Khurram, Muhammad; Javed, Saima; Khaar, Hamama tul Bushra; Goraya, M Fayyaz; Hasan, Zubair (Journal of Rawalpindi Medical College, 2026)
Background: To study etiology of upper gastro-intestinal [GI] haemorrhage with flexible upper GI endoscopy. Methods: 2484 patients who were endoscoped at DHQ Teaching Hospital, Rawalpindi, from October to December 2003, for evaluation of upper GI haemorrhage were included. Record of these patients that included patient characteristics, endoscopic diagnosis etc was analyzed using statistical program, SPSS version 8. Results: Of the 2484 patients, 68% were female and 32% male. Mean patient age was 38.8 ± 12.6 years. Erosive gastritis [15.6%], esophago/gastro/duodenitis [15.3%], duodenitis [14.7%], varices [12.9%], and peptic ulcer disease [8.3%] were commonest endoscopic diagnosis. 24% patients had normal upper GI endoscopy. Conclusion: Erosive gastritis, esophago/gastro/duodenitis, duodenitis, varices, and peptic ulcer disease are common causes of upper GI haemorrhage in our patients.